MULTI-REPRESENTATION-BASED E-MODULE ANALYSIS OF NEEDS IN THEME 3 SUBTEMA 1 IN 6TH GRADE ELEMENTARY SCHOOL - Kurniasari, Dita; Susanti, Rahmi; Siahaan, Sardianto Markos (JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
This research aims to analyze the needs of electronic modules (E-Modules) based on multi-representation using Flipbook PDF Professional. At this stage, researchers made observations and collected data on teaching materials at SDN 146 Palembang. This research uses a questionnaire with qualitative data types as the data collection. The data analysis technique used is descriptive analysis with data reduction, data presentation, conclusion, and verification. The data that needs to be analyzed by researchers are data regarding the use of the types of teaching materials used, the implementation of learning, the evaluation system, and the factors that support it. Based on the questionnaire data, 46.7% of students thought the learning material for theme 3, sub-theme 1, which discussed inventors who changed the world, could have been more interesting. Students stated this because 73.3% answered that no exciting teaching materials could make the material easily understood by students. Furthermore, based on the distribution of needs analysis questionnaires related to the e-module teaching materials to be developed, students with a percentage of 76.7% answered that they needed teaching materials that contained images, text, video, and audio or sound. E-Modules can be an alternative in developing teaching materials to support improving the quality of learning.